Skill-Biased Imports, Skill Acquisition, and Migration - Jingting Fan; Lei Li (Institute of Labor Economics (IZA), 2023)
Imported capital goods, which embody skill-complementary technologies, can increase the supply of skills in developing countries. Focusing on China and using a shift-share design, we show that city-level capital goods import growth increases the local skill share and that both skill acquisition and migration play a role. We develop and quantify a spatial equilibrium model with these two mechanisms to examine the aggregate effects of capital goods imports, accounting for trade and migration linkages between cities. Counterfactual experiments suggest that the growth in capital goods imports in China between 2000 and 2010 led to a 3.7-8.9 million increase in the stock of college graduates, representing 5.7-13% of the total increase over this period. However, this growth disproportionately favored coastal regions, exacerbating existing spatial disparities.
Keywords: F14; F16; F66; J24; J61; 330; imported capital goods; capital-skill complementarity; skill acquisition; migration